Mild Cognitive Impairment Subtypes Are Associated With Peculiar Gait Patterns in Parkinson’s Disease - Amboni, Marianna; Ricciardi, Carlo; Cuoco, Sofia; Donisi, Leandro; Volzone, Antonio; Ricciardelli, Gianluca; Pellecchia, Maria Teresa; Santangelo, Gabriella; Cesarelli, Mario; Barone, Paolo (Frontiers in Aging Neuroscience, 2022)
Background: Mild cognitive Impairment (MCI) is frequent in Parkinson Disease (PD) and represents a risk factor for the development of dementia associated with PD (PDD). Since PDD has been associated with disability, caregiver burden, and increase in health-related costs, early detection of MCI associated with PD (PD-MCI) and its biomarkers is crucial. Objective: Given that gait is considered a surrogate marker for cognitive decline in PD, the aim of the present study was to compare gait patterns in PD-MCI subtypes in order to verify the existence of association between specific gait features and particular MCI subtypes. Methods: Sixty-seven PD patients were consecutively enrolled and assessed by an extensive clinical and cognitive examination. Based on neuropsychological exam, patients were diagnosed as patients with (PD-MCI) and without MCI (no-PD-MCI) and classified in MCI subtypes. All patients were evaluated using a motion capture system of BTS Bioengineering equipped with six infrared digital cameras. Patients’ gait was assessed in the on state under three different tasks (a single task and two dual tasks). Statistical analysis included t-test, Kruskal Wallis test with post hoc analysis and an exploratory correlation analysis. Results: Gait pattern was poorer in PD-MCI versus no-PD-MCI in all tasks. Among PD-MCI subtypes, multiple domain PD-MCI and amnestic PD-MCI were coupled with worse gait patterns, notably in dual task. Conclusions: Both the magnitude of cognitive impairment and the presence of memory dysfunction are associated with increased measures of dynamic unbalance, especially in dual task conditions, likely mirroring the progressive involvement of posterior cortical networks.